Investigação das outras disfluências em indivíduos gagos em diferentes faixas etárias - Alonso, Sarah Pereira [UNESP] (2021)
Other disfluencies are common disruptions to all speakers, including those who stutter and mainly reflect linguistic uncertainties and inaccuracies, aiming at expanding the understanding of the message. They can be classified as: interjection, hesitation, revision, unfinished words, phrase repetition, and non-monosyllabic word repetition. There are investigations on the prevalence and justifications for their occurrence of individuals' speech with typical development, syndromes or communication disorders. However, there is a gap in the national and international literature regarding the analysis of other disfluencies observed in the speech of individuals who stutter. The general objective of this study was to investigate and compare the frequency and typologies of other disfluencies in individuals diagnosed with neurodevelopment stuttering, in different age groups. 146 individuals from a database of the Laboratory of Studies, Evaluation and Diagnosis in Speech-Language Pathology (LEAD) and the Fluency Studies Laboratory (LAEF) participated. The participants were subdivided by lifespan, in four groups: Preschool Children Group (PCG), consisted of 40 children from 3 to 5 years old; School Children Group (SCG), consisted of 62 children from 6 to 9 years old; Adolescent Group (AG), consisted of 18 individuals aged 10 to 19 years old; Adult Group (ADG), consisted of 26 individuals aged 20 to 59 years. All participants underwent a speech fluency evaluation, using audiovisual records of the spontaneous speech sample with 200 fluent syllables and classified according to the Stuttering Severity Instrument - SSI-3 Protocol. Statistical analysis was conducted using SPSS version 20 software, with a significance level of 0.05. Results showed that the adult had a higher number of other disfluencies in relation to the preschool children group. The groups were similar regarding frequency of hesitation, this being the most prevalent typology in all groups. The interjection occurred more frequently in the adult group when compared to children, preschool children or school children. The revision typology was more prevalent in adults and school children when compared to preschool children. The repetition of speech segment occurred more frequently in adolescents when compared to preschool children, and they showed a lower amount of non-monosyllabic word repetition in relation to adolescents. Unfinished words occurred more frequently in school children than in preschool children. Therefore, it is concluded that the group of adults who stutter showed a higher frequency of other disfluencies, when compared to preschool children who stutter, specifically a higher number of interjection and revision. The number of other disfluencies interfered with the total number of disruptions in the flow of speech of individuals who stutter, regardless the age group. It is believed that these other disfluencies should be valued in the fluency evaluation and therapy to provide a reduction and consequent promotion in fluency and an improvement in the communication of these individuals.